The Management of Advanced Training of Engineering and Technical Specialists Based on the Interaction Between Universities and Business-Structures - Nikitin A. A. Aleksandr Aleksandrovich; Palyanov M. P. Mikhail Pavlovich; Morozova M. V. Marina Vyacheslavovna; Markovichev A. S. Aleksandr Sergeevich (2016, 2016)
Title screen